Decellularized Porcine Saphenous Artery for Small‐Diameter Tissue‐Engineered Conduit Graft. Issue 6 (9th April 2013) - Xiong, Yun; Chan, Wing Yue; Chua, Alvin W.C.; Feng, Jiajun; Gopal, Pamela; Ong, Yee Siang; Song, Colin
Abstract Decellularized xenografts have been identified as potential scaffolds for small‐diameter vascular substitutes. This study aimed to develop and investigate a biomechanically functional and biocompatible acellular conduit using decellularized porcine saphenous arteries (DPSAs), through a modified decellularization process using Triton X‐100/NH4OH solution and serum‐containing medium. Histological and biochemical analysis indicated a high degree of cellular removal and preservation of the extracellular matrix. Bursting pressure tests showed that the DPSAs could withstand a pressure of 1854 ± 164 mm Hg. Assessment of in vitro cell adhesion and biocompatibility showed that porcine pulmonary artery endothelial cells were able to adhere and proliferate on DPSAs in static and rotational culture. After interposition into rabbit carotid arteries in vivo, DPSAs showed patency rates of 60% at 1 month and 50% at 3 months. No aneurysm and intimal hyperplasia were observed in any DPSAs. All patent grafts showed regeneration of vascular elements, and thrombotic occlusion was found to be the main cause of graft failure, probably due to remaining xenoantigens. In conclusion, this study showed the development and evaluation of a decellularization process with the potential to be used as small‐diameter grafts.